The influence of the anode overhang effect on the capacity of lithium-ion cells – a 0D-modeling approach. (June 2020) - Fath, Johannes Philipp; Alsheimer, Lennart; Storch, Mathias; Stadler, Jochen; Bandlow, Jochen; Hahn, Severin; Riedel, Ralf; Wetzel, Thomas
Highlights: Effect of the anode overhang on cell capacity at different storage conditions. Evaluation of the overhang effect with experimental three electrode cells. Modeling the time depending capacity variation. Influence of different separator materials on reversible capacity fading. Abstract: In this work, the behavior of the anode overhang effect in lithium-ion cells is experimentally investigated and simulated for experimental three electrode cells. An empirical method is presented to transfer the simple 0D-model from the experimental cell level to pouch cells. An anode overhang model will help to correctly interpret cyclic and calendaric aging experiments e.g. in terms of a more reliable and detailed separation of reversible and irreversible capacity losses as well as evaluating the actual state of health of a lithium-ion battery. For the three electrode cells different cathode diameters are used to modulate different sized anode overhang areas. Moreover, the influence of different state of charges on the reversible capacity effect is investigated. To examine the influence of the separator on the evolution of usable cell capacity different separator thicknesses are applied. It is found that the properties of the separator significantly influence the rate at which balancing processes between overhang and active region take place. The results show good accordance of the experimental results to the simulation. Graphical abstract: Image, graphical abstract